Ideologiczne i prawne podstawy tworzenia systemu pracy w pierwszych miesiącach istnienia Polski Ludowej - Kania, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In Marxist ideology, work was one of the fundamental ideas. It formed an important element of the basis of the entire system of views, as well as the socio-economic system built on its basis. This position was taken over by the Polish communists who, with the publication of the PKWN Manifesto, began their march for power in post-war Poland. In their conception of the system of people’s democracy, work took the central place of the new axiological order. The aim of the article is to present the relationship between the idea of work contained in the ideology and program of Polish communists and the law-making activity defining the principles of performing work in the early period of the existence of People’s Poland.
Keywords: work; Marxism-Leninism; Polish communists; People’s Poland; people’s democracy